Chemical composition and efficacy in the egg-hatching inhibition of essential oil of Piper aduncum against Haemonchus contortus from sheep - Oliveira,Gisele Lopes (2014)
Piper aduncum L., Piperaceae, has been used to treat mainly inflammatory diseases and has shown several biological activities such as insecticidal and larvicidal. The aim of this study was to analyze the chemical composition of essential oil of P. aduncum and its efficacy to egg-hatching inhibition of Haemonchus contortus from sheep. The essential oil was obtained from leaves and analysed by gas chromatography coupled to flame ionization detector and gas chromatography coupled to mass spectrometry. It was possible to characterize 22 different substances, among them monoterpenes (80.6%) and sesquiterpenes (13.9%). The major compound was identified as 1,8-cineole (55.8%). Eggs of the nematode were exposed to four concentrations of the essential oil. Levamisole phosphate was used as positive control. The essential oil showed to be effective in inhibiting H. contortus hatchability and the LC90 was calculated as 8.9 mg.ml-1. These results can point out the P. aduncumessential oil and its chemical components as potential alternative to control of H. contortus